Experimental study of boiling on nanostructured surfaces - Muhammad Abul Barakaath (Nanyang Technological University, 2022)
One of the most efficient heat transfer methods is through nucleate boiling where it is beneficial in many industrial applications for the purpose of cooling electronic devices and much more. Hence, there is a lot of research being done in this area to continuously enhance the heat transfer rates in nucleate boiling. It is known that the modifications of surface roughness have a positive impact of the enhancement of the heat transfer rate. There has been past research that has been done using smooth surface and surfaces with coatings. However, not much has been done in the areas of fabricated well-arranged nanostructured surfaces.